Evaluation of Drug and Food Education Information Communication Strategy in Special Schools in the Special Region of Yogyakarta - Wulandari, S.T.P., M.I.Kom., Wulandari (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2024)
BBPOM in Yogyakarta took the initiative expanding the scope of communication, information, and education (KIE) for Drugs and Food by implementing KIE in special schools (SLB). The purpose of this study is toensure that educational messages can be delivered in a way that is appropriate and effective for the SLB community. With this evaluation, the effectiveness of communication strategies can be assessed, obstacles identified, influences analyzed, and perceptions of the SLB community regarding the IEC program that has been implemented can be explored.The research is in the form of an evaluation (Evaluation Research), using quantitative methods with surveys via questionnaires and document studies, based onbased on the IEC dimensions in Decree Number 104 of 2022 concerning Guidelines for Information and Education Communication Strategies, namely target group strategy, creative, message, media amplification, activity program, and implementation of IEC. The survey was conducted on 7 SLBs that had received IEC during 2023 to April 2024. The respondents numbered 135 consisting of students, principals, teachers, employees, and canteen managers. The strategies implemented received good assessments from respondents, namely target group strategy 86.1%, creative 85.1%, message 82.4%, media amplification 85.0%, activity program 84.2%, and implementation of IEC 84.7%, there was input for IEC to be implemented periodically and it was necessary to exemplify the review of food in schools. The IEC strategy for Drugs and Food in SLB by BBPOM in Yogyakarta is good and appropriate. The implementation of IEC for SLB in DIY can be accelerated with a tiered method, namely providing training to representatives of each SLB first. Constraints related to limited student abilities can be overcome by developing more creative, interesting, and specific educational materials according to the needs of the SLB community.